Improving recruitment to pharmacological trials for illicit opioid use: findings from a qualitative focus group study - Neale, Joanne (Addiction, 2018)
AIM: To explore potential study participants’ views on willingness to join clinical trials of pharmacological interventions for illicit opioid use to inform and improve future recruitment strategies. DESIGN: Qualitative focus group study [six groups: oral methadone (two groups); buprenorphine tablets (two groups); injectable opioid agonist treatment (one group); and former opioid agonist treatment (one group)]. SETTINGS: Drug and alcohol services and a peer support recovery service (London, UK). PARTICIPANTS: Forty people with experience of opioid agonist treatment for heroin dependence (26 males, 14 females; aged 33–66 years). MEASUREMENTS: Data collection was facilitated by a topic guide that explored willingness to enrol in clinical pharmacological trials. Groups were audio‐recorded and transcribed. Transcribed data were analysed inductively via Iterative Categorization. FINDINGS: Participants’ willingness to join pharmacological trials of medications for opioid dependence was affected by factors relating to study burden, study drug, study design, study population and study relationships. Participants worried that the trial drug might be worse than, or interfere with, their current treatment. They also misunderstood aspects of trial design despite the researchers’ explanations. CONCLUSIONS: Recruitment of participants for clinical trials of pharmacological interventions for illicit opioid use could be improved if researchers became better at explaining clinical trials to potential participants, dispelling misconceptions about trials and increasing trust in the research process and research establishment. A checklist of issues to consider when designing pharmacological trials for illicit opioid use is proposed.